An investigation of diet management strategies for the culture of the South African abalone, Haliotis midae - Simpson, Brynn James Alric (Department of Biological Sciences, 2024)
The Far East provides an almost insatiable market for a wide variety of seafood products. Abalone are one of the more sought after delicacies of the East due to the subtly flavoured meat. Abalone are imported from around the world and command high prices. Throughout their global distribution, many of the I 00 or so species of abalone are commercially and recreationally exploited. The continuing demand for abalone has resulted in the overexploitation of wild stocks throughout the world. ·Most commercial abalone fisheries are characterised by high yields at the beginning of the fishery, followed by a subsequent decline in yields to present levels (Ebert, 1992; Tarr, 1992). Abalone culture was pioneered in Japan, partly as a consequence of overexploitation, through the development of reseeding programmes.· Hatchery-reared abalone were reseeded into depleted wild abalone populations, and are now harvested sustainably by •· i local fishermen (Shaw, 1982). Similar ventures have been investigated for Haliotis tuberculata by Cochard and Flassch (1981), H. rufescens by Ebert and Ebert (1988) and Tegner and Butler (1989), H. kamtschatkana by Emmet and Jamieson (1988), and H. iris by Schiel (1993). In addition to reseeding programmes, abalone culture has provided new products for the Far East seafood markets. Abalone are exported live from several countries, as 'cocktail abalone' and command prices in excess of those paid for canned or frozen abalone (Rudd, 1994). H. midae is highly sought after in the Far East (Rudd, 1994). In South Africa, wild populations of abalone have been commercially exploited since 1949 (Tarr, 1992). The only abalone of commercial value is Haliotis midae, which is distributed between St Helena Bay (320 45'S~ 180 IO'E) on the West coast and just Chapter 1. Introduction 2 north of Port St Johns (31 o 40'S; 2.90 35'E) on the East coast of South Africa (Wood, 1993). H. midae is most abundant between St Helena Bay and Cape Agulhas (Barkai and Griffiths, 1986) and supports a commercial fishery between Cape Columbine and. Quoin Point (Tarr, 1992). A small commercial fishery exists at Hamburg on the East coast of South Africa (Wood, 1993). Research into culture of the South African abalone began in the last decade, encouraged by the decline in wild abalone populations and the development of a market for cocktail sized abalone. Initially abalone culture was not considered to be viable in South Africa, largely due to a lack of knowledge. The initial breakthrough in the culture of H. midae followed the demonstration that it was possible to spawn wild abalone through chemical cues (Genade et al., 1988). The realization that the spawning and culture of H. midae was possibl~ prompted further research into abalone culture. At present there are approximately 10 commercial companies involved in the preliminary stages of abalone culture in South Africa. Globally, research has covered many aspects of abalone culture. In the present study, various aspects of growth and nutrition of cultured H. midae were researched.